A direct proof that toric rank 2 bundles on projective space split - Stapleton, David (MATHEMATICA SCANDINAVICA, 2020)
The point of this paper is to give a short, direct proof that rank 2 toric vector bundles on n-dimensional projective space split once n is at least 3. This result is originally due to Bertin and Elencwajg, and there is also related work by Kaneyama, Klyachko, and Ilten-Süss. The idea is that, after possibly twisting the vector bundle, there is a section which is a complete intersection.